Determinasi Sosial Demografi terhadap Literasi Digital pada Petani di Wilayah Pesisir Kabupaten Bone Bolango - Amin, Nur Silfiah; Sirajuddin, Zulham; Arsyad, Karlena (Universitas Galuh, 2026)
The need to use digital technology to access agricultural information does not always align with the ability of coastal farmers to utilize digital media for improving their farm production. Digital literacy serves as a catalyst in fostering independence, sustainability, and competitiveness among farmers, particularly in coastal areas that often face limited access to information and infrastructure. The objective of this study is to identify the level of digital literacy among coastal farmers and to examine which socio-economic characteristics influence their digital literacy. This research employs a mixed-methods approach combining qualitative and quantitative methods. The qualitative approach involves in-depth interviews to explore farmers’ experiences related to the use of technology, while the quantitative approach applies multiple linear regression analysis to assess the influence of demographic factors on the level of digital literacy among coastal farmers. The findings reveal that demographic factors have varying effects on farmers’ digital literacy. Partially, age shows a significant negative effect, indicating that the older the farmers, the lower their digital literacy. Conversely, education level has a significant positive effect, meaning that higher education correlates with better digital literacy skills. The number of family dependents also shows a relatively weak but significant positive effect, suggesting that household responsibilities may motivate farmers to use digital technology to improve their welfare. Meanwhile, gender, land size, and farming experience are not found to have a significant impact. In conclusion, age and education are the dominant factors shaping farmers’ digital literacy, whereas other demographic variables do not provide meaningful influence.